Hate Speech in social media: An Exploration of the Problem and its proposed Arrangement in India - Showkat Ahmad Dar; Aadil Ahmad ShairGojri (Zien Journals, 2021)
National Integration is the obligation of each citizen. The public reconciliation is tested on account of the untrustworthy exercises of citizens. As India is a multicultural, multi religious, multiparty and caste-based country, it is entirely defenceless against different issues and these issues challenge national integration. In the period of digital entrance the greater part of the untrustworthy exercises against national integration are occurring in web-based media stage. The constitution of India through its various legislations and CrPC made an honest effort to contain Hate speech addresses in online media stages, for example, Facebook, Twitter, LinkIndia, WhatssApp, YouTube and so on However, when Supreme Court made it unlawful on grounds of abusing the right to speak freely of speech and, the quantity of hate speech expanded in India and it caused for some issues in the public arena.
Keywords: objectionable content; social media platform; Freedom of Speech; National Integration